PERANAN KOMUNIKASI KELUARGA DALAM MENCEGAH PERKELAHIAN ANTAR WARGA (Studi Kasus Di Kelurahan Mahakeret Barat) - Sambuaga, Dewi Pingkan (ACTA DIURNA KOMUNIKASI, 2014)
Abstract. Role Of Communications Family In Preventing Fight Between Citizen (Case Study In Sub-District of Mahakeret West). Sub-District of Mahakeret West located in down town of Manado and represent one of the 12 sub-district exist in district of Wenang. Mahakeret West of is included in one of the target of object of wisata exist in Sulawesi North because [in] this sub-district there are fossil situs in the form of old grave people of Minahasa first inhabit town of Manado. In perception cusorily tawuran/fight between citizen often happened because of some factor for example, namely the lack of informal communications and interaction in family, assocciation of too free children so that many is adolescent/involved in young man usage of forbidden drugs and alcoholism even often happened action of premanisme because lack of old fellow control to assocciation of child also because lack of education storey;level of children. As for formula of is Problem of: 1) This Internal issue Research is limited byrole of communications family in preventing fight between citizen; 2) Problem formula to check is how role of family communications in preventing fight between citizen. Keyword : Role, Communications, Family